Dynamic real-time capacity constrained routing algorithm for evacuation planning problem - Jawad Abusalama; Sazalinsyah Razali; Yun-Huoy Choo; Lina Momani; Abdelrahman Alkharabsheh (Institute of Advanced Engineering and Science, 2020)
Usually, disasters occur over a relatively short time anytime and anywhere. Most occupancies do not have absolute knowledge about the prevention or safety consciousness to deal with disasters. During disaster occurrence, evacuation processes are conducted to save people’s life, and if there is no appropriate evacuation plan, the situation will become worse. Thus, finding an optimal planning technique to evacuate occupants is critical in many cases i.e. emergency evacuation. In this paper, a Dynamic Real-Time Capacity Constrained Routing (DRTCCR) Algorithm has been proposed and analyzed. Such algorithm will investigate the capacity constraints of the evacuation network in real time by modelling the capacities based on time series to improve current solutions of the Emergency Route Planning (ERP) problem. Such algorithm will produce an optimal solution for the ERP problem. Performance evaluation on many network models illustrates that the DRTCCR algorithm improves the previous evacuation planning by reducing the evacuation time as well as the computational cost. In addition, DRTCCR algorithm has the ability to recalculate and find out the optimal path dynamically in real time irrespective of the number of trapped people as well as the transportation network size. Analytical experiments have been carried out, which illustrates the efficiency of the proposed algorithm.